Development of a "banana candy" using banana (Musa paradisiaca) peel flour as a fiber supply. - Araujo C., Valeria P. (Zamorano: Escuela Agrícola Panamericana, 2025)
The reuse of agricultural by-products to enhance the nutritional value of food products is currently a growing trend being implemented by the industry. Bananas are considered the fourth most important food crop globally, with Ecuador ranked among the top producers. The peel, which is rich in fiber and antioxidants, accounts for 30% of the fruit. This project evaluated the addition of banana peel flour to a traditional Ecuadorian dessert called banana candy to increase its fiber content. The objectives were to assess the effect of this addition on the sensory, physical characteristics, and fiber content of the dessert. Affective sensory evaluation was conducted using an acceptance and preference test with 100 panelists, where color, smell, taste, sweetness, texture, and overall acceptance of four treatments with different levels of banana peel flour (0%, 5%, 7.7%, and 10%) were evaluated. A Randomized Complete Block Design (RCBD) was used, an ANOVA and a Duncan mean separation were applied to determine the treatment with the highest acceptance. Physicochemical analyses were performed on the control and the 5% banana peel flour treatment using an Independent Samples Design and a t-test. The results showed that the 5% banana peel flour treatment was the most accepted after the control, significantly increasing the fiber content, although it did not meet the levels required to be considered a source of fiber according to the RTCA.